PENGARUH TEKANAN ANGGARAN WAKTU, KOMPLEKSITAS TUGAS, DAN KARAKTERISTIK PERSONAL TERHADAP PERILAKU DISFUNGSIONAL AUDIT PADA KANTOR AKUNTAN PUBLIK DI KOTA DENPASAR. - Ida Ayu Made Surya Wardani; Kadek Dewi Padnyawati; Putu Nuniek Hutnaleontina (UNHI Press, 2021)
Public accountants are accountants who have obtained permission from the minister of finance to provide public accounting services in Indonesia. There are many cases of auditor failure that have occurred proving that the role of an auditor is still not optimal and because the level of auditor satisfaction has not been fulfilled by the Public Accounting Firm (KAP) which causes a decrease in performance and damage to public and corporate client confidence in the Public Accounting Firm (KAP ). This study aims to determine the effect of time budget pressure, task complexity, personal characteristics on dysfunctional audit behavior at public accounting firms in Denpasar. This study took 55 respondents who were used as research samples using purposive sampling method. Data colection was carried out throught interviews, observations, and questionaires. The data analysis technique used is multiple linear analysis. The results of the analyze showing that time budget pressure has a regression coefficients of 0.321 with a t-sig of 0.004, which means that time budget pressure has a positive effect on audit dysfunctional behavior. Task complex has a regression coefficient of 0.289 with a t-sig of 0.002, which meaning that task complex has a positive effects on dysfunctional audit attitude. Personal characteristics have a regression coefficient value of 0394 with a t-sig of 0.001, which means that personal characteristics have a positive effect on dysfunctional audit behavior at KAPs in Bali.